A double whammy effect of ethnicity and gender on consumer responses to management level service failures. Issue 3 (20th June 2016) - Wu, Laurie; Han, Rachel; Mattila, Anna S
Abstract : Purpose: – Existing research on demographic stereotypes of employees suggests that ethnicity and gender are important determinants of consumer perceptions and behaviors. Based on the Stereotype Content Model and the Role Congruity Theory, the purpose of this paper is to examine the effect of ethnicity and gender stereotypes on management-level service failures in a US context. Design/methodology/approach: – Adopting a 2 (ethnicity: Caucasian vs Hispanic) × 2 (gender: male vs female) between-subjects design, two studies were conducted with US consumers to test whether a double whammy effect of ethnicity and gender exists for management-level, but not line-level, service failures. Findings: – The results of this study suggest that Hispanic female managers suffer from a double whammy effect due to ethnic and gender-based stereotyping in the USA. Furthermore, the findings indicate that the serial mediation via competence perceptions and blame attributions are the underlying psychological mechanism of this effect. As predicted, occupational status functions as a boundary factor to the double whammy effect. Originality/value: – The findings of this paper contribute to the service management literature by examining the role of demographic characteristics in influencing US consumers' responses to management-level service failures.